Electrical properties of ferroelectric Y-doped Hf–Zr–O thin films prepared by chemical solution deposition. (1st November 2022) - Sasaki, Keisuke; Mohit,; Hashiguchi, Sho; Tokumitsu, Eisuke
Abstract: Y-doped Hf–Zr–O (Y-HZO) films have been prepared by chemical solution deposition. It is shown that good ferroelectric property can be obtained for the Y-HZO film with a Y concentration of 3.2% after 800 °C crystallization annealing at a reduced pressure of 50 Pa. It is also demonstrated that the reduced pressure pre-annealing at temperatures as low as 400 °C is effective to obtain good ferroelectric properties, regardless of the crystallization annealing ambient. This is presumably because the pre-annealing under reduced pressure promotes the formation of nuclei in the orthorhombic phase.